2006
DOI: 10.1136/tc.2005.013292
|View full text |Cite
|
Sign up to set email alerts
|

Cost of tobacco-related diseases, including passive smoking, in Hong Kong

Abstract: Background: Costs of tobacco-related disease can be useful evidence to support tobacco control. In Hong Kong we now have locally derived data on the risks of smoking, including passive smoking. Aim: To estimate the health-related costs of tobacco from both active and passive smoking. Methods: Using local data, we estimated active and passive smoking-attributable mortality, hospital admissions, outpatient, emergency and general practitioner visits for adults and children, use of nursing homes and domestic help,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 32 publications
2
52
2
2
Order By: Relevance
“…The ratio of SHS costs to active smoking costs in our study was higher than a study conducted in Hong Kong, which reported a ratio of 29%. 25 Our study demonstrates that the true impact of smoking on healthcare costs in rural areas would be one third higher than the estimates by Yang et al 24 when the burden of SHS exposure is included. Given that the majority of women and children are nonsmokers and exposed to SHS in rural China, tobacco control interventions that reduce SHS exposure are needed.…”
Section: Discussioncontrasting
confidence: 45%
“…The ratio of SHS costs to active smoking costs in our study was higher than a study conducted in Hong Kong, which reported a ratio of 29%. 25 Our study demonstrates that the true impact of smoking on healthcare costs in rural areas would be one third higher than the estimates by Yang et al 24 when the burden of SHS exposure is included. Given that the majority of women and children are nonsmokers and exposed to SHS in rural China, tobacco control interventions that reduce SHS exposure are needed.…”
Section: Discussioncontrasting
confidence: 45%
“…Also worthy of mention is the cost of second-hand smoke and of perinatal conditions, particularly the former, that have been included in the calculation of economic burden in a number of countries 42,43 . The comparison of our findings with those of other investigations that estimated costs for the health system is limited, due to aspects that were mentioned in a previous research 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco dependence is a chronic disease that is responsible for over 6900 deaths a year in Hong Kong 1 and nearly 6 million deaths a year worldwide. It is also the single most important preventable risk factor responsible for death and chronic disease, including cancer and cardiovascular diseases.…”
Section: Present Policymentioning
confidence: 99%